Impact of foreign direct investment flows to the Eastern Caribbean Central Bank unified currency area. - WILLIAMS, Oral (1999)
Attempts to analyse trends in foreign direct investment flows to the ECCB region during the period 1986-96 and to evaluate the impact of FDI on a number of macroeconomic aggregates.